Apreliminary study of intra-pocket topical versusinjected anaesthetic for scaling and root planing - Jill L. Stoltenberg (Blackwell Synergy, 2007)
Aim: Compare the efficacy of topical benzocaine gel to injected lidocaine during scaling and root planing. Materials and Methods: In each of 21 participants undergoing root planing, two dental quadrants were randomly assigned to receive topical 20% benzocaine gel delivered subgingivally (TOP) or injection anaesthesia using 2% lidocaine (INJ). Baseline, intra- and immediate post-operative pain was assessed using the Heft–Parker pain scale. Intra-subject differences (INJ–TOP) were analysed using paired t-tests and mixed models. Results: Baseline and post-operative pain did not differ between treatments (p40.50). The injected anaesthetic, however, was associated with less intra-operative pain than the topical (INJ–TOP5 24.9 mm, p50.005) Six participants required rescue (injected) anaesthesia during treatment with the topical. Eleven participants (52%) preferred topical over injected anaesthetic. Among these 11, intra-operative pain scores did not differ significantly (TOP538.6 mm, INJ528.4 mm, p50.23). Among those who preferred the injected anaesthetic, intra-operative pain scores differed significantly (TOP584.7 mm, INJ543.8 mm, p50.03). Conclusions: Intra-pocket benzocaine gel is less effective than injected lidocaine in controlling pain during scaling and planing. Anaesthetic preference was related to the level of pain experienced during treatment with the topical. Larger studies are needed to confirm these findings.